Implementación de las normas internacionales de información financiera (niif) para pymes en la empresa “Sifizsoft s.a” ubicada en la provincia de Pichincha, cantón Quito, parroquia el Batán del 01 de enero al 31 de diciembre del 2012 - Guaña Casa, Diana Paola (2015)
This research topic was developed in the company Sifizsoft SA, dedicated to providing technology services to financial institutions with the aim of presenting financial statements under IFRS SMEs through adjustments, reclassifications and changes required in the process of implementing the 2012, as a small business I am part of the third group had to apply these rules on schedule issued by the Superintendency of Companies. In which he spoke of the relevant characteristics of the company, which use different methods to help detect unnecessary procedures in Financial Statements, applying the different phases, the process of implementation of the rules on each account where relevant changes were reflected performed they came to adopt these standards and thus specific changes in accounting policies. Which brings us understand that the application of the IFRS for SMEs was not only changes in accounting but involves the participation of the entire entity, with innovative technology to change accounting mentality, resulting in efficient work and the ability to compare financial information globally, transparency and trust for shareholders, and position in the international market.